DISCOURSE, LAW, AND DIGITAL COMMUNICATION: Unraveling the Hate Speech in Basuki Tjahaja Purnama’s Case of Religious Blasphemy (State Islamic University (UIN) of Sunan Ampel Surabaya, 2023)
The article examines hate speech, particularly religious insults, and its implications in the case of Basuki Tjahaja Purnama or Ahok, the former Governor of Jakarta. It underscores the complexity of regulating cyberspace expressions, especially on social media, and calls for clear legal regulations to prevent social conflict. It highlights the real-world impact of online hate speech and the role of linguistic analysis in addressing it. The analysis is in three stages. The first is a text and context analysis using the Discourse-Historical Approach (DHA), examining Ahok's speech within historical and discursive contexts. The second focuses on Indonesia's legal frameworks governing hate speech. The third analyzes the court proceedings in Ahok's hate speech case, using both micro and macro linguistic approaches. The article concludes with two main points; the need to analyze the intent behind hate speech and recommends a dual-dimension linguistic analysis model in judicial processes related to hate speech cases, including religious insults. By embedding this component within the legal criteria, it becomes possible to achieve a more holistic and equitable assessment of hate speech cases. Overall, the article provides a nuanced analysis of hate speech, its real-life implications in Ahok's case, and the need for refined legal and judicial approaches to address hate speech.